Remeber the natural log rules:
ln(a*b) = ln(a) + ln(b)
ln(a/b) = ln(a) - ln(b)
ln(a^b) = b*ln(a)
Break that ln(2x) down into ln(2) + ln(x).
int[ln(2) + ln(x)]dx = int[ln(2)*dx] + int[ln(x)*dx]
Since ln(2) is a constant, it'll just integrate into x*ln(2).
You would need to use integration by parts on int[ln(x)*dx].
In case you don't remember or haven't learned it yet, integration by parts go like this by product rule:
d(uv) = u*dv + v*du
int[d(uv)] = int[u*dv + v*du] = int[u*dv] + int[v*du]
--> uv = int[u*dv] + int[v*du]
--> int[u*dv] = uv - int[v*du]
Let u = ln(x) and dv = dx.
du = (1/x)dx
v = int(dv) = int(dx) = x
int[ln(x)dx] = x*ln(x) - int[x*(1/x)dx] = x*ln(x) - int(dx)
= x*ln(x) - x + C
int[ln(2x)dx] = int[ln(2) + ln(x)]dx = int[ln(2)*dx] + int[ln(x)*dx]
= x*ln(2) + x*ln(x) - x + C
=x[ln(2) + ln(x)] - x + C
=x[ln(2x)] - x + C
=ln[(2x)^x] - x + C
2007-04-05 11:07:38
·
answer #1
·
answered by Anonymous
·
0⤊
0⤋
The answer is
x ( ln2x -1/2)
2007-04-05 10:43:46
·
answer #2
·
answered by Sarkasme 2
·
0⤊
0⤋
I will show each and every step as you requested. 2·∫ x·ln(2x) dx u = ln(2x) du = [1/x] dx dv = x dx v = ½·x² ∫ u dv = uv - ∫ v du 2·∫ x·ln(2x) dx = 2·[ ½·x²·ln(2x) - ∫ ½·x²·[1/x] dx 2·∫ x·ln(2x) dx = 2·[ ½·x²·ln(2x) - ½·∫ x dx] 2·∫ x·ln(2x) dx = 2·[ ½·x²·ln(2x) - ¼·x²] + C 2·∫ x·ln(2x) dx = x²·ln(2x) - ½·x² + C
2016-05-18 00:27:00
·
answer #3
·
answered by tamra 3
·
0⤊
0⤋
Why not try Google. It also act as a real top notch calculator as well as a search engine!
2007-04-05 10:36:20
·
answer #4
·
answered by lavito 3
·
0⤊
1⤋
Let u = ln(2x), du = 2dx/x
dv = dx, v = x
∫ln(2x)dx = xln(2x) - ∫2xdx/x = xln(2x) - 2x + C
2007-04-05 10:56:45
·
answer #5
·
answered by Helmut 7
·
0⤊
0⤋
integration(ln(2x) dx) = (x*ln(2x)) - x + constant
2007-04-05 10:51:13
·
answer #6
·
answered by Ahmed 1
·
0⤊
0⤋